Successful Retrieval of a 4-Year-Old Micra Transcatheter Pacemaker System in a Patient With Leadless Biventricular Pacing Therapy - Kentaro Minami, MD; Jürgen Shtëmbari, MD; Jan Petrů, MD; Milan Chovanec, MD; Moritoshi Funasako, MD; Pavel Hála, MD; Marek Janotka, MD; Jan Škoda, MD; Lucie Šedivá, MD, PhD; Vivek Y. Reddy, MD; Petr Neužil, MD, PhD (JACC: Case Reports, 2020)
This is the first report of the management of a patient with cardiac resynchronization therapy using leadless biventricular pacing. Successful retrieval of a 4-year-old Micra transcatheter pacing system (TPS) and reimplantation of a new Micra TPS prevented device-to-device interactions from multiple pacing devices in the right ventricle. (Level of Difficulty: Advanced.)